Protection of Industrial Design Rights against the Imitation of Local Fashion Products - Indah Sari Br. Barus; Qori Asvifah Bintang; Wahdaniah Sitorus; Sukri padil dongoran (ISNU Sumatera Utara, 2026)
The rise of design imitation in local fashion products causes losses for creative industry players, especially industrial design rights holders. Industrial design as part of Intellectual Property Rights has an important role in protecting the aesthetic value and innovation of a product. This study aims to analyze the regulation and legal protection of industrial design rights for local fashion products imitated based on Law Number 31 of 2000 concerning Industrial Design. The research method used is normative legal research with a legislative and conceptual approach. The results of the study show that Law Number 31 of 2000 has provided legal protection to industrial design rights holders through the granting of exclusive rights, both preventively and repressively. However, in practice, the legal protection still faces various obstacles, such as low awareness of business actors in registering industrial designs and weak law enforcement. Therefore, efforts to increase legal awareness and law enforcement are needed more effectively to protect local fashion products from imitation of designs.